On the Use of Authentic Professional Texts while Teaching Еnglish - O.V. Novikova (Язык и текст, 2022)
The article focuses on using authentic texts of a professional orientation in the process of teaching English to environmental students. The need to authenticate the education of students is argued by giving the example of students at environmental (engineering and environmental) faculties. There is a classification of authentic materials that can be applied at various levels of education. It is concluded that while studying vocational-oriented English, environmental students can master a wide range of competencies, including a stable foreign-language professional communicative one.